The Influence of Culture on Attitudes Towards Humorous Advertising - Wang, Yi; Lu, Su; Liu, Jia; Tan, Jiahui; Zhang, Juyuan (Frontiers in Psychology, 2019)
Humor has been widely used in advertising in recent decades. Various studies found that humor could significantly improve advertising performance. However, most of these studies were conducted in western context and did not consider cultural factors. In a cross-cultural research framework, the current study explored the effects of advertisement characteristics (i.e., brand nationality and humor tactics) on Chinese and US audiences’ attitudes towards humorous advertisements. Results showed that the attitudinal differences between Chinese audience and US audience was not significant at the aggregate level. Instead, the differences lie in audience’s responsiveness to characteristics of the ads. Specifically, whereas US audience showed a strong preference for ads of Chinese brand to those of US brands, Chinese audience did differentiate them. Whereas US audience preferred ads using self-enhancing tactics to those using affiliative tactics, again Chinese audience didn’t differentiate. We also explored whether individual differences in cultural values could account for the effect of audience nationality. Results suggest that differences embedded in culture groups, as indicated by audience nationality, could not be explained or substituted by individual variance in humor tolerance and uncertainty avoidance. Limitations and future directions were discussed.